Penerapan Sistem Informasi Akuntansi Dan Teknologi Informasi Pada Penjualan CV. Sentral Elektrindo Perkasa - Fajri Mustofa Akbar; Hotbin Hasugian; Budi Dharma (STIKes Ibnu Sina Ajibarang, 2023)
This research is to determine the application of accounting information systems and information technology to CV case study sales. Sentral Elektrindo Perkasa. This research uses qualitative research methods and data collection techniques using interview and documentation techniques. This research uses data collection techniques by interviewing several employees at CV. Sentral Elektrindo Perkasa. The results of this research indicate that the implementation of the Accounting Information System at CV. Sentral Elektrindo Perkasa has started to improve and meets standards, however routine control and supervision is very necessary so that things do not happen that could be detrimental to the company. And Application of Information Technology in CV. Sentral Elektrindo Perkasa has a very important role in bringing out the best potential from employees and also has an important role in the company achieving its goals and being able to increase sales potential optimally.